Confirmation : an analysis and assessment - Maker, Derek Alan (Rhodes University, Faculty of Divinity, Department of Divinity, 1967)
Intelligently to discuss Christian initiatory rites we must begin with Baptism. In recent years many scholars have attempted a critical re-assessment of baptism based upon a renewed exegetical study of the New Testament. This chapter is written in the light of that work. Most theologians are agreed upon the cardinal importance of baptism. Calvin is generally representative in saying, "Baptism is a sign of initiation, by which we are admitted into the society of the Church, in order that, being incorporated into Christ we may be numbered among the children of God". Wheeler Robinson, a Baptist theologian, asserts that, "Baptism is the door of entrance to the Church". Intro. p. 1.
Keywords: Confirmation